Orthodontic management of transposed tooth, impacted and ectopic canines, midline shifting and crossbite correction by fabrication of a CAD/CAM made temporary bite raising crown. (Bangladesh Journal of Medical Science, 2026)
Background Patients presenting with transposed tooth are relatively rare and the aim of the Orthodontist is to manage a healthy, functional, and aesthetically acceptable dentition. The consequences of transposed tooth, impacted and ectopic canines, midline shifting, crossbite include an abnormal occlusion or an altered facial appearance which may lead to psychological distress in some patients. Methods The present case report describes a 16 year old Saudi female patient with non-syndromic, transposed tooth, impacted and ectopic canines, midline shifting and crossbite. Clinical examinations revealed multiple malalignment problems. Following fabrication of a CAD/CAM made temporary bite raising crown [TBRC] used to unlock the bite to correct the crossbite #12 and open coil spring to open the space for transposed lateral and other problems corrections are managed using fixed orthodontic braces. Results Innovative new technique used to unlock the bite using TBRC to correct the #12 crossbite. Transposed #42 managed successfully after open up the space using NiTi open coil coil spring. Conclusion A combined TBRC and Fixed Orthodontic treatment approach can achieve an improved favourable healthy, aesthetics and functioning occlusion.Bangladesh Journal of Medical Science Vol. 25 No. 03 July’26 Page: 983-988